Emotional Intelligence and Job Satisfaction among Faculty Members of Higher Education Institutions of Pakistan - Arain, Muhammad Waqas; Rahoo, Nawab; Thebo, Jalil Ahmed; Khan, Muhammad Ali; Rahoo, Liaquat Ali (The journal of contemporary issues in business and government, 2021)
The aim of this study is to measure the correlation between emotional intelligence and job satisfaction of the faculty members of public sector higher education institutions of Sindh province. The method of this study is descriptive with quantitative design. The population of the studycompriseshigher education institutions of Sindh province. A random sampling technique is used to collect primary data with a questionnaire. Participants are recruited through survey sampling using “Google Forms”. Faculty members having teaching experience of more than five years in higher education institutions of Sindh province are included in the study.Data is entered and analyzed using SPSS version 20.Results reveal about strong positive and statistically significant correlation between emotional intelligence and job satisfaction. Moreover, this positive and statistically significant correlation was seen between job satisfaction and all components of emotional intelligence. All qualities of emotional intelligence, as well as overall emotional intelligence scores, showed a significant positive correlation with job satisfaction scores; which were statistically significant; p<0.05.There was a statistically significant positive correlation between all components of emotional intelligence and job satisfaction. Hence, it is important for higher education institutions to concentrate on those practices that promote emotional intelligence among their teaching faculty.